The Nature Of Educators In The Context Of Islamic Education - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2025)
In the context of Islamic education, there are several terms for educators, such as mu'allim, ustadz, murabbi, muyrsid, mudarris, and mu'addib. Each term has a different meaning, depending on the context of the sentence, although in certain situations there are similarities in meaning between them. The word